Syria's Democratic Years : Citizens, Experts, and Media in the 1950s - Martin, Kevin W. (Book collections on Project MUSE., 2015)
The years 1954-1958 in Syria are popularly known as "The Democratic Years," a brief period of civilian government before the consolidation of authoritarian rule. Kevin W. Martin provides a cultural history of the period and argues that the authoritarian outcome was anything but inevitable. Examining the flourishing broadcast and print media of the time, he focuses on three public figures, experts whose professions-law, the military, and medicine-projected modernity and modeled the new Arab citizen. This experiment with democracy, however abortive, offers a model of governance from Syria's historical experience that could serve as an alternative to dictatorship.